Is underuse of Inhaled Corticosteroids for Asthma in India contributing to 42% of global asthma deaths? - Sundeep Salvi; Sapna Madas; Deesha Ghorpade; Swapnil Gadhave; Monica Barne (Lung India, 2022)
Background: According to the 2019 Global Burden of Disease (GBD) report, India contributes to an estimated 12.9% of global asthma cases (34.3 million) but a disproportionate 42.3% of all global asthma deaths. Also, asthma causes 4.83 million disability-adjusted life years (DALYs) annually in India, four times more than China, which ranks second. Hypothesis: We hypothesised that this disproportionate increase in asthma deaths and suffering in India could be due to the under-use of inhaled corticosteroids. Methods: Using the estimated number of asthma cases in each state and union territory in India (34.3 million) from the 2019 GBD data, we calculated the expected sales of inhaled corticosteroids (ICS) for asthmatics in India. We assumed that 10% of asthmatics have mild intermitted disease and thus need only 4 units of ICS pMDI per year. The remaining 90% should ideally use 12 units of ICS pMDI or equivalent DPI. We also assumed that 30% of ICS sales in India would be accounted for by the 38 million COPD patients. State-wise actual sales of ICS in India were obtained from IQVIA. Results: The total amount of ICS sales in India for asthma obtained from IQVIA was 26.4 million versus the 384.16 million expected sales, which is only 6.8% of the required estimated sales. Moreover, when we correlated state-wise actual sales of ICS in India versus asthma mortality and DALYs (per 100,000 population), we found a significant negative correlation (R = −0.56; P < 0.001 for asthma deaths and R = −0.61; P < 0.001 for asthma DALYs). Impact and Future Direction: Policy-makers, health care providers, public health researchers, asthma sufferers and the people at large need to take cognizance of our findings and undertake appropriate measures, such as creating awareness and ensuring availability and regular use of ICS by asthmatics in India.